Integrating Sustainability into Community-Based Blue Accounting: Evidence from East Kalimantan’s Coastal Tourism - Yunita Fitria; Mega Norsita; Muhammad Rinaldi; Sitti Rahma Sudirman; Diah Fitri Harseno (Penerbit Goodwood, 2026)
Purpose: This study investigates how sustainability principles are integrated into community-based blue accounting practices across coastal tourism sites in East Kalimantan, Indonesia. While sustainability accounting has been widely discussed at the national and corporate levels, limited studies have explored how these concepts emerge in grassroots tourism governance. Research Methodology: The study adopts an interpretive qualitative case study approach involving three destinations: Pantai Lamaru (Balikpapan), Bontang Kuala (Bontang), and Pantai Panrita Lopi (Muara Badak). Data were collected through interviews, observations, and document analyses. Results: The findings revealed that sustainability is manifested through environmental stewardship, community empowerment, and cultural preservation. Each site has informal but functional reporting systems that reflect transparency, participation, and collective accountability. Although blue accounting has not yet been implemented, several elements of blue accounting, such as participatory reporting, environmental monitoring, and community accountability, are already practiced informally. These practices demonstrate how local communities embed sustainability values in tourism governance and financial decision-making. Conclusions: Sustainability values serve as an underlying driver of community-based reporting and participatory governance, indicating the early formation of blue accounting elements within grassroots tourism contexts and highlighting the need for institutional support to strengthen future formalization of blue accounting. Limitations: The research focused on three sites in one province and used qualitative data, limiting generalization. Contributions: This study contributes to the sustainability accounting literature by demonstrating that grassroots tourism governance can serve as an early form of blue accounting in developing coastal regions.